Review of organic functional groups : Introduction to medicinal organic chemistry - Lemke, Thomas L.; Zito, S. William; Roche, Victoria F (London: Lippincott Williams & Wilkins, 2012)
"This self-paced review enables you to master the principles and applications of organic functional groups. Moreover, it prepares you for the required pharmacy courses in medicinal chemistry by covering nomenclature, physical properties, chemical properties, and metabolism. As you progress through the text, you'll develop such important skills as drawing chemical structures and predicting the solubility, instabilities, and metabolism of each organic functional group."
1 Water Solubility and Chemical Bonding2 Alkanes (CnH2n+2)3 Alkenes (CnH2n)4 Aromatic Hydrocarbons5 Haolgenated Hydrocarbons6 Alcohols7 Phenols8 Ethers and Thioethers9 Aldehydes and Ketones10 Amines11 Carboxylic Acids12 Functional Derivatives of Carboxylic Acids13 Sulfonic Acids and Sulfonamides14 Nitrogen Functional Groups15 Heterocycles16 Oligonucleotides and Nucleic Acids17 Proteins18 Predicting Water SolubilityA Steroisomerism-Asymmetric MoleculesB Acidity and BasicityC Drug MetabolismD Learning ObjectivesIndex
Student workbook CD-ROM features problem sets corresponding to each of the organic functional groups covered in Chapters 2 to 17
Keywords: Organic Chemistry, Pharmaceutical chemistry